Environmental conditions predetermine quality, germination, and innate antioxidants pool in sea oat (Uniola paniculata L.) seeds - Egesa, Andrew Ogolla; Pérez, Héctor E.; Begcy, Kevin (Frontiers in Environmental Science, 2023)
Secondary metabolites such as antioxidants are critical components that protect seeds from stress damage during seed development, desiccation, and ex-situ storage.Antioxidants are essential determinants of seed quality, longevity, and persistence.Understanding the environmental factors that regulate the accumulation, content, and function of antioxidant pools in sea oat seeds is critical for gene banking and understanding the environmental impacts on seed quality. Germination, viability, and Trolox Equivalent Antioxidant Capacity (TEAC) were analyzed on seeds from 18 sea oat populations from the US Atlantic and Gulf of Mexico coasts. We first assessed baseline TEAC, followed by TEAC performed on imbibed seeds for 36 hours at 35/25 °C during the day and night, respectively. Then, we analyzed the relationship of the antioxidant pools from these 18 sea oat populations to sampling site environmental classifications. Higher baseline antioxidants were common in regions with extreme environmental conditions corresponding to sea oat populations growing at latitudinal extremes characterized by warmer and colder temperatures. Baseline antioxidants did not correlate with prevailing seed germination. However, higher concentrations of antioxidants following imbibition were associated with poor seed germination in warmer conditions. Our results indicate that climatic conditions and environmental components associated with temperatures and precipitation may largely influence the innate pool of antioxidants in sea oat seeds. Also, a high amount of antioxidants following sea oat seeds imbibition suggest seed damage or poor viability influenced by environmental stress conditions during seed development.